ANZAED practice and training standards for dietitians providing eating disorder treatment - Gabriella Heruc; Susan Hart; Garalynne Stiles; Kate Fleming; Anjanette Casey; Fiona Sutherland; Shane Jeffrey; Michelle Roberton; Kim Hurst (Journal of Eating Disorders, 2020)
Abstract Introduction Dietitians involved in eating disorder treatment are viewed as important members of the multidisciplinary team. However, the skills and knowledge that they require are not well characterised. Therefore, as part of a broader project to identify the key principles and clinical practice and training standards for mental health professionals and dietitians providing eating disorder treatment, the Australia & New Zealand Academy for Eating Disorders (ANZAED) sought to identify the key practice and training standards specific to dietitians. An expert working group of dietitians was convened to draft the initial dietetic standards. After expert review, feedback on the revised standards was then provided by 100 health professionals working within the eating disorder sector. This was collated into a revised version made available online for public consultation, with input received from treatment professionals, professional bodies and consumer/carer organisations. Recommendations Dietitians providing treatment to individuals with an eating disorder should follow ANZAED’s general principles and clinical practice standards for mental health professionals and dietitians. In addition, they should also be competent in the present eating disorder-specific standards based around the core dietetic skills of screening, professional responsibility, assessment, nutrition diagnosis, intervention, monitoring and evaluation. Conclusions These standards provide guidance on the expectations of dietetic management to ensure the safe and effective treatment of individuals with an eating disorder. Implications for professional development content and training providers are discussed, as well as the importance of clinical supervision to support professional self-care and evidence-informed and safe practice for individuals with an eating disorder.